2019
DOI: 10.12669/pjms.36.2.1194
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of suprachoroidal triamcinolone acetonide in cases of resistant diabetic macular edema

Abstract: Objective: To evaluate the safety and efficacy of Suprachoroidal Triamcinolone Acetonide (SCTA) injection in patients with treatment resistant Diabetic Macular Edema (DME). Methods: This was a prospective non randomized interventional study conducted in the vitreoretinal department of Al Ehsan Welfare Eye Hospital, Lahore, Pakistan from March 2018 to September 2018. A total of 24 eyes of 24 patients were included. Baseline Best Corrected Visual Acuity (BCVA), Intra Ocular Pressure (IOP) and Central Subfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
3
8
2
2
Order By: Relevance
“…In our study, the improvement in CMT and BCVA was significant until the third month of post-injection in the IV and the 4 mg SC groups, which agreed with Tayyab et al, 20 who injected 4 mg SCTA into treatment-resistant DME, and had significant CMT and BCVA improvements at 1 and 3 months, although they did not follow the patients till 6 months to detect the persistence of this improvement. While Yousef et al had persistent significant improvement in CMT and BCVA till 6 months post-injection of 4 mg SCTA contradicting our results, we had definite regression in CMT in the 4 mg SCTA group at 6 months, although BCVA was relatively stable compared to 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the improvement in CMT and BCVA was significant until the third month of post-injection in the IV and the 4 mg SC groups, which agreed with Tayyab et al, 20 who injected 4 mg SCTA into treatment-resistant DME, and had significant CMT and BCVA improvements at 1 and 3 months, although they did not follow the patients till 6 months to detect the persistence of this improvement. While Yousef et al had persistent significant improvement in CMT and BCVA till 6 months post-injection of 4 mg SCTA contradicting our results, we had definite regression in CMT in the 4 mg SCTA group at 6 months, although BCVA was relatively stable compared to 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…This elevation in the IOP may be due to higher IOP before injection or a large steroid dose. We also found that suprachoroidal TA is effective for treating DME, which agrees with the nding of Tayyab et al, [11], who included 24 patients with DME and found a signi cant rise in the BCVA and decrease in the Central Sub eld Thickness over three months follow-up.…”
Section: Summary Of the Main Ndingssupporting
confidence: 92%
“…However, targeting the DME from the suprachoroidal space using triamcinolone acetonide may be effective. For persistent cases of DME in particular, 22 as the suprachoroidal space is full of aqueous and is 1 ml in volume, 23 the triamcinolone should be cleared from the suprachoroidal space within 8 weeks. 24 Targeting the suprachoroidal space may offer increased triamcinolone efficacy, as it will be less diluted in the suprachoroidal space versus the vitreous cavity, with less interaction with the angle of the anterior chamber.…”
Section: Discussionmentioning
confidence: 99%